Cancer in Elderly Onset Inflammatory Bowel Disease: A Population‐Based Study. (October 2016) - Cheddani, Halima; Dauchet, Luc; Fumery, Mathurin; Charpentier, Cloé; Bouvier, Anne Marie; Dupas, Jean‐Louis; Pariente, Benjamin; Peyrin‐Biroulet, Laurent; Savoye, Guillaume; Gower‐Rousseau, Corinne
Abstract : OBJECTIVES: Cancer may be a complication of inflammatory bowel disease (IBD) or its treatment. In elderly onset IBD patients the risk of malignancy is of particular concern. We studied this risk in a population‐based cohort of elderly onset IBD patients. METHODS: In a French population‐based cohort, we identified 844 patients aged >60 years at IBD diagnosis from 1988 to 2006, including 370 Crohn's disease (CD) and 474 ulcerative colitis (UC). We compared incidence of cancer among IBD patients with that observed in the French Network of population‐based Cancer Registries (FRANCIM). Confidence interval (CI) was estimated assuming a Poisson‐specific law for rare events. Results were expressed using the standardized incidence ratios (SIRs) and their CI 95%. RESULTS: Median age at IBD diagnosis was 70 (65–76) years in CD and 69 (64–74) in UC. Median follow‐up was 6 (2–11) years for both diseases with a number of person‐years of 5, 598. Among the 844 elderly onset IBD cases, 98 (11.6%; 42 CD and 56 UC) developed a cancer after IBD diagnosis (67 men and 31 women) corresponding to an overall SIR of 0.97 (0.80–1.18). These cancers occurred at a median age of 77 years (71–80) and 75 years (71–81) in patients with CD and UC, respectively. Median time between IBD diagnosis and cancers was 78 months (40–121). There was no significant increased risk of colorectal cancer in IBD (SIR=1.03 (0.62–1.70), CD (SIR=1.20 (0.57–2.52) nor in UC (SIR=0.91 (0.45–1.82) without significant protective role of 5‐aminosalicylic acid (hazard ratio (HR)=0.7 (0.2–2.6)). No significant risk for other intestinal cancers was found, especially for small bowel carcinoma. An increased risk of malignant lymphoproliferative disorders was found in all IBD and in CD: SIR=2.49 (1.25–4.99) and SIR=3.09 (1.16–8.23), respectively. An increased risk of myeloproliferative disorders was found in all IBD (SIR=2.18 (1.09–4.35)). Thiopurines exposure, using a time‐dependant Cox model, was not found as associated with an increased risk to develop cancer, HR=0.90 (0.48–1.68). CONCLUSIONS: There is no increased risk for developing intestinal cancer among patients with elderly onset IBD in this population‐based cohort. There are increased risks of developing lymphoproliferative and myeloproliferative disorders in all IBD. Thiopurines exposure was not found as associated with an increased risk to lymphoproliferative disorders. These data reinforce the difference between elderly onset IBD as compared with patients with younger age at IBD onset.